the original problem was: (sin x + cos x)^2 + (sin x - cos x)^2 = 2steps too pleaseI got 1 for (sin x + cos x)^2 but then what does (sin x - cos x)^2 become since it's minus?
Dont copié formé thé book oh ya dont copié formé thé book cause you Oiil inde up being triste soi remembré not toi copié frome thé book oh ya!translation in english please!
GOT A 102 ON FACS SPELLING TEST GOT 100 ON FACS TEST GOT A 94 ON MATH TEST GOT 80 ON MATH NTBK QUIZ GOT 100 ON ENG POSTER GOT 87 ON SCI HW GOT A CHECK ON SCI HW/CW GOT A 93 AEVRAGE FOR SSGOT A 87 AVERAHE FOR SCI (for the 2nd quarter 1st quarter i got a 80 so i done some rlly grea...
find all solutions in the interval [0,2 pi) sin(x+(3.14/3) + sin(x- 3.14/3) =1 sin^4 x cos^2 xSince sin (a+b) = sina cosb + cosb sina and sin (a-b) = sina cosb - cosb sina, the first problem can be written 2 sin x cos (pi/3)= sin x The solution to sin x = 1 is x = pi/2 For your o...
Can you check my answers:2) 5/8 - 1/4i got: 3/84) 1 1/2 - 2 4/5i got: 7/106) 5 7/8 + 3 5/12i got: 9 7/2410) 3 1/2 + 2 2/5i got: 5 9/1018) 6 7/12 + 4 5/12i got: 1120) 7 9/10 + 3 3/10i got: 11 1/522) 18 3/8 + 11 6/7i got: 30 13/5624) 26 9/10 + 72 5/6i got: 99 1...
2 times the square root of x minus 1 minus the square root of 3x minus 5 equals the square root of x minus 9
the original problem was:Solve: sin(3x)-sin(x)=cos(2x)so far i've gooten to:sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x)Where would I go from here?
the original problem was: Solve: sin(3x)-sin(x)=cos(2x) so far i've gotten to: sin(x)(2sin(x)cos(x)-1)=cos^2(x)-sin^2(x) Where would I go from here?
log(square root of 1-x) - log(square root of x+2)=logx First I sqared both sides and got log 1-x -log x+2=log x squared then i performed the quotient property of logs and got log(1-x/x+2)=log x squared then I got 1-x =x squared (x-2) then I got X cubed - 2x+ x-1=0
Solve the following equation for 0 less than and/or equal to "x" less than and/or equal to 360--cos^2x - 1 = sin^2x--Attempt:cos^2x - 1 - sin^2x = 0cos^2x - 1 - (1 - cos^2x) = 0cos^2x - 1 - 1 + cos^2x = 02cos^2x - 2 = 0(2cos^2x/2)= (-2/2)cos^2x = -1cosx = square root of -1And I c...
cos(tan + cot) = csconly simplify one side to equal cscso far I got this far: [((cos)(sin))/(cos)] + [((cos)(cos))/(sin)] = cscI don't know what to do next
Simplify this complex rational expression: 8 divided by x square minus 4x minus 21 minus 1 divided by x+3 then all of the above divided by 1 divided by x-7 plus 1 thank you :)